2019
DOI: 10.3389/fonc.2019.01143
|View full text |Cite
|
Sign up to set email alerts
|

Lactate in the Regulation of Tumor Microenvironment and Therapeutic Approaches

Abstract: Tumor cells must generate sufficient ATP and biosynthetic precursors in order to maintain cell proliferation requirements. Otto Warburg showed that tumor cells uptake high amounts of glucose producing large volumes of lactate even in the presence of oxygen, this process is known as "Warburg effect or aerobic glycolysis." As a consequence of such amounts of lactate there is an acidification of the extracellular pH in tumor microenvironment, ranging between 6.0 and 6.5. This acidosis favors processes such as met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
535
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 654 publications
(546 citation statements)
references
References 192 publications
10
535
0
1
Order By: Relevance
“…Intratumoral lactate levels seem to be prognostic in several cancers. In fact, it has been demonstrated that high lactate levels are associated with higher incidence of distant metastasis in different cancer types [11], although the mechanism is not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Intratumoral lactate levels seem to be prognostic in several cancers. In fact, it has been demonstrated that high lactate levels are associated with higher incidence of distant metastasis in different cancer types [11], although the mechanism is not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Lactate is formed exclusively from pyruvate regardless of oxygen availability, and robustly exported to the TME, reaching concentrations that can be 20-fold higher (about 40 mM) (74) than in non-tumoral tissues (about 1.5-3 mM) (13,15). Lactate is a major fuel source, providing energetic and anabolic support to cancer cells, and an important oncometabolite with both extracellular and intracellular signaling functions that equally contribute to cancer progression (Figure 1) (75,76).…”
Section: Lactate Roles In the Tumor Microenvironment: From Metabolicmentioning
confidence: 99%
“…Interestingly, the levels of lactate were inversely correlated with the levels of glucose, and directly correlated with the expression of MCT4. Later studies have also linked intratumoral lactate levels with higher incidence of distant metastasis and poor patient survival (76).…”
Section: Lactate Metabolism As a Prognostic And Therapeutic Toolmentioning
confidence: 99%
“…Intrinsic traits (e.g., genetic programs in cancer cells) and extrinsic factors (e.g., nutrient availability, oxygen tension, pH) contribute to the deregulated metabolism in TME. TME enforces metabolic plasticity to adapt to hypoxic and acidic environment, nutrient deprivation and competition, oxidative stress, and immune surveillance (52). Reprogramming of the metabolism occurs in tumor and non-tumor cells.…”
Section: Glucose Metabolism and Tumor Microenvironment (Tme)mentioning
confidence: 99%